2017
DOI: 10.1039/c7ra07995h
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic water oxidation at amorphous trimetallic oxides based on FeCoNiOx

Abstract: The rapid electrochemical formation of amorphous FeCoNiOxis reported which is both active and stable for the oxygen evolution reaction under alkaline conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
34
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 50 publications
4
34
0
Order By: Relevance
“…Two minor peaks were found in the XRD spectrum of the NiS x sample after the OER at 2θ=32.2 and 37.2 which can be indexed as the (101) and (111) planes of crystalline NiS (JCPDS 12‐0041) and NiO respectively (ICDD file number 47‐1049). The generation of a crystalline material from an amorphous precursor as a result of the OER has been observed previously for FeCoNiO x . However, the NiP x material remained amorphous after OER cycling.…”
Section: Resultssupporting
confidence: 73%
“…Two minor peaks were found in the XRD spectrum of the NiS x sample after the OER at 2θ=32.2 and 37.2 which can be indexed as the (101) and (111) planes of crystalline NiS (JCPDS 12‐0041) and NiO respectively (ICDD file number 47‐1049). The generation of a crystalline material from an amorphous precursor as a result of the OER has been observed previously for FeCoNiO x . However, the NiP x material remained amorphous after OER cycling.…”
Section: Resultssupporting
confidence: 73%
“…It was shown that an amorphous shell on Co 3 O 4 is the active form for catalysis which returns to a crystalline state upon return to open circuit potential conditions . It appears here that a largely amorphous material can also form a more crystalline material once the catalytic reaction is ceased and is also consistent with previous work on an electrodeposited amorphous FeCoNiO x material . This will have implications in a commercial sense for electrolysers that are connected to intermittent renewable energy sources that may be subjected to rapid start up and shut down conditions.…”
Section: Resultssupporting
confidence: 88%
“…The electrochemical fabrication of electrocatalytically active nanomaterials is also an area of intense interest given the simplicity, scalability and cost effectiveness of the approach compared to other chemical synthesis routes that may require multiple steps and the use of high temperature or pressure to achieve the desired material . In the area of water splitting electrocatalysts, electrodeposited materials are often amorphous which in many instances show enhanced activity over their crystalline counterparts due to the large number of defect or low co‐ordination number sites which are highly desirable for electrocatalytic activity . A continuous challenge with these materials is balancing the high activity of the catalyst with long term stability.…”
Section: Introductionmentioning
confidence: 99%
“…created a catalytically active FeCoNiO x H y amorphous material. The trimetallic catalyst is more active than any single or bimetallic oxide combination towards OER as a result of the synergetic effect among the three components . Despite some progress has been approached, discovery of novel trimetallic catalysts toward OER with stable operation and low overpotentials in alkaline media are still requisite.…”
Section: Introductionmentioning
confidence: 99%
“…The trimetallic catalyst is more active than any single or bimetallic oxide combination towards OER as ar esult of the synergetic effect among the three components. [12] Despite some progress has been approached,d iscoveryo fn ovel trimetallic catalysts toward OER with stable operation andl ow overpotentials in alkaline mediaare still requisite. Herein,wereport the fabrication of aseries of Co 1-X Fe X Ni-oxidized carbon nanocubes (Co 1-X Fe X Ni-OCNC) derived from MOFs, in whicht he molar ratios of Fe and Co can be precisely tuned.…”
Section: Introductionmentioning
confidence: 99%